Mean time to recruitment for three grades with two sources of depletion - Rojamary, T.; Uma, K. P.; Anuradha, K. (EAI Endorsed Transactions on Energy Web, 2018)
In any organization when the policy decisions related to emoluments, benefits and objectives are announced then the exit of personnel is occurred. When the exit of personnel occurs, time overwhelming and expense happened for the recruitment , so that the recruitment cannot introduced in real time and also frequent recruitment are not encouraged, when the cumulative loss of manpower on critical occasion cross the level called as threshold, then only the recruitment is introduced and made. A mathematical model is developed using univarity policy of recruitment based on shock model approach in this paper. The inter-policy decision times and the inter-transfer decision times form same renewal process for three grades to obtain the mean variance of the time to recruitment. Mathematical equations for mean time to recruitment are developed using Laplace transform.